2014
DOI: 10.1287/moor.2013.0618
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Limits for Bandwidth-Sharing Networks in Overload

Abstract: Bandwidth-sharing networks as considered by Roberts and Massoulié [28] (Roberts JW, Massoulié L (1998) Bandwidth sharing and admission control for elastic traffic. Proc. ITC Specialist Seminar, Yokohama, Japan) provide a natural modeling framework for describing the dynamic flow-level interaction among elastic data transfers. Under mild assumptions, it has been established that a wide family of so-called α-fair bandwidth-sharing strategies achieve stability in such networks provided that no individual link is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Results of a similar nature may also be found in Lemma A.3 of Kelly and Williams (2004) and Proposition 4.1 of Borst et al (2014). These authors, respectively, established continuity and Lipschitz continuity of · defined above for special cases, with no rate constraints.…”
Section: The Bandwidth Allocation Mechanism and Its Propertiessupporting
confidence: 59%
See 1 more Smart Citation
“…Results of a similar nature may also be found in Lemma A.3 of Kelly and Williams (2004) and Proposition 4.1 of Borst et al (2014). These authors, respectively, established continuity and Lipschitz continuity of · defined above for special cases, with no rate constraints.…”
Section: The Bandwidth Allocation Mechanism and Its Propertiessupporting
confidence: 59%
“…Fundamental papers on fluid limit approximations for bandwidth-sharing networks are Kelly and Williams (2004) and Gromoll and Williams (2009). Properties of overloaded bandwidth-sharing networks have subsequently been derived by Borst et al (2014) and Egorova et al (2007). A diffusion approximation for bandwidth-sharing networks was derived in Kang et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…By adapting techniques from [12], it can be shown that this assumption holds in the linearized Distflow model. Proposition 1.…”
Section: Fluid Approximationmentioning
confidence: 99%
“…In order to prove uniqueness of a (0, a)-solution, we derive a proper estimate for it via solutions with other parameters. The whole idea of this proof is adopted from [4].…”
Section: Proposition 1 (Gronwall Inequality) Suppose That Functions Umentioning
confidence: 99%